Non-Inseminated Queens Have Worker-Like Behaviors in Colonies of Fungus-Growing Ants, Mycetomoellerius turrifex Wheeler (Attini, Hymenoptera) - Murakami, Takahiro (Sociobiology, 2020)
In  eusocial  Hymenoptera  such  as  ants,  bees,  and  wasps,  the  queen  numbers  are  fundamentally  important  to  maintain  the  social  systems.  In  Texas,  USA,  a  fungus  growing  ant,  Mycetomoellerius  turrifex  Wheeler  (1903)  (the  genus  name  was  changed from Trachymyrmex to Mycetomoellerius in 2019 (Solomon et al., 2019)) was  observed  to  have  several  non-inseminated  queens  that  wandered  outside  the nest long after the mating season. However, the evolutionary and ecological factors causing the occurrence of such non-inseminated queens are still unclear. Thus,  I  examined  the  worker-like  behaviors  of  non-inseminated  queens  of  M. turrifex in Texas. Fifteen ant colonies were collected over three years, between 1999 and 2001. The frequencies of non-inseminated queens, workers, and broods, as well as the depths of nest chambers, were observed in each collecting year. In Nov. 1999 and May 2000, multiple nests contained queens that did not mate with males within their nests. These nests had a relatively larger colony size than those collected in Oct. 2001. Conversely, the colonies collected in Oct. 2001 were completely monogynous, i.e., there were no non-inseminated queens in the nests. Behavioral observations of each female revealed that the non-inseminated queensbehaved significantly differently from the workers and the inseminated queens. The behaviors that distinguished different female castes were mutualistic fungus garden care, digging of nest floors, guarding, and resting in the nest. These data suggest that queens failed to mate due to severe environmental fluctuations in southern Texas, but were accepted by the colony as a temporary labor force.